Composite phase change material as well as preparation method and application thereof
By using a double porous adsorption and strong magnetic attraction pulling system in building materials, combined with organic phase change materials and magnetic powders, a composite phase change material is formed, which solves the problems of leakage, low thermal conductivity and poor stability when used in building materials, and achieves efficient thermal energy storage and release.
Patent Information
- Application Number
- CN202411688170.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-03-04
AI Technical Summary
The existing phase change materials have problems such as leakage, low thermal conductivity and poor stability when used in building materials, which limits their practicality in building materials.
By adopting a pull-up system of double porous adsorption and strong magnetic attraction, combined with organic phase change materials, activated carbon powder, expanded perlite powder and magnetic powder, a composite phase change material is formed, achieving high integrity and cyclic stability.
It significantly improves the efficiency of thermal energy storage and release, improves the stability and application performance of phase change materials, and reduces energy waste.
Smart Images

Figure BDA0005150182340000051
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of composite materials, and in particular relates to a composite phase change material and a preparation method and application thereof. Background Art
[0002] At present, gypsum-based self-leveling mortar is usually used as the "floor heating" leveling covering layer. It does not produce cracking, bulging and other phenomena due to thermal expansion and contraction like cement mortar layer, so it has been widely used. However, the use of gypsum-based self-leveling mortar as the "floor heating" leveling covering layer has disadvantages such as large temperature fluctuations and energy waste. Thermal energy storage can not only effectively reduce the mismatch of energy supply in time and space, but also enable thermal energy to be effectively managed and utilized. Therefore, applying phase change materials to gypsum-based self-leveling mortar is an effective way to achieve energy storage.
[0003] Phase change materials are divided into inorganic phase change materials and organic phase change materials. Inorganic phase change materials are mainly divided into hydrated salts and metal alloys. Hydrated salts have the problem of supercooling during the phase change process, and nucleating agents are often required to be added, resulting in high costs. The phase change temperature of metal alloys is generally above 300°C, which is not suitable for conventional use scenarios. Organic phase change materials mainly use the phase change material to absorb heat when it changes from solid to liquid within a certain temperature range, and then release heat when it changes from liquid to solid to store heat. Phase change materials are prone to leakage and low thermal conductivity during the process of changing from solid to liquid or from liquid to solid within a certain temperature range, which limits their application in building materials. Therefore, phase change materials need to be encapsulated before use to ensure the stability of phase change materials in the solid-liquid process and improve the practicality of phase change materials in building materials. The main encapsulation methods currently under research include: impregnation method, porous adsorption method and microencapsulation method. The impregnation method requires the control of parameters such as solvent selection, temperature, flow rate, etc. to ensure that the material can be evenly distributed. The operation process of this method is relatively complicated and requires fine control and operation skills. The microencapsulation process is complex and has high economic cost. The porous adsorption method can not only solve the leakage problem of phase change materials, but also greatly improve the stability of phase change composite materials.
[0004] CN 104152114 B uses natural inorganic porous materials as carriers to load hydrated salt phase change materials, prepares hydrated salt-porous carrier composites by adding nucleating agents, then wraps the hydrated salt-porous carrier composites with water-soluble silicon or water glass, dehydrates to prepare hydrogel-coated hydrated salt-porous material composite phase change energy storage materials, and then mixes with gypsum to obtain phase change gypsum slurry, and the phase change gypsum slurry is compounded and formed with fiber filaments, mesh cloth, etc. to obtain phase change gypsum. Although the isolation of hydrated salt phase change materials and gypsum is achieved, and the leakage and migration problems of hydrated salts are improved, hydrated salts have the problem of supercooling during the phase change process, and nucleating agents are often required to be added, resulting in high costs and not suitable for large-scale use.
[0005] The shaped phase change material for construction in CN 113788648 A is composed of dodecyl alcohol and stearic acid adsorbed in an optimal mass ratio in modified diatomite treated with negative pressure, and Al2O3 nanoparticles are additionally added to optimize thermal conductivity. However, this shaped method has poor stability and still has leakage problems. How to further improve the adsorption stability of organic phase change materials in porous adsorption materials has become a technical problem to be solved urgently. Summary of the invention
[0006] The purpose of the present invention is to provide a composite phase change material and its preparation method and application. Through the bonding system of double porous adsorption and strong magnetic attraction, the obtained composite phase change material has a high degree of integrity and cycle stability. At the same time, the magnetic material can be used as a middle layer medium to realize internal and external conduction, thereby achieving a significant improvement in the efficiency of thermal energy storage and release.
[0007] In order to achieve the above purpose, the technical solutions adopted are as follows:
[0008] A composite phase change material, the composition of which is as follows in parts by weight:
[0009] 52-62 parts of organic phase change material, 60-65 parts of activated carbon powder, 50-70 parts of expanded perlite powder, 17-28 parts of N-pole magnetic powder, and 17-28 parts of S-pole magnetic powder.
[0010] According to the above scheme, the organic phase change material is a compound of paraffin and fatty acid organic phase change material, the phase change temperature is 29°C, the phase change latent heat value is 220J / g, and the thermal conductivity is 0.2W / (m·K); wherein the fatty acid phase change material is one of lauric acid, capric acid, stearic acid, myristic acid, palmitic acid, and acetic acid.
[0011] According to the above scheme, the particle size of the activated carbon powder is 0.7-0.8 mm, the pH value is 3-7, and the pore size is 0.1-0.11 mm.
[0012] According to the above scheme, the expanded perlite has a particle size of 3-5 mm and a density of 0.8 g / cm 3 , the pore size is 1-1.5mm.
[0013] According to the above scheme, the N-pole magnetic powder is one of samarium cobalt magnetic powder, ferrite magnetic powder, neodymium iron boron magnetic powder, aluminum nickel cobalt magnetic powder, and titanium nickel iron magnetic powder, and the particle size is 0.02-0.04mm.
[0014] According to the above scheme, the S-pole magnetic powder is one of samarium cobalt magnetic powder, ferrite magnetic powder, neodymium iron boron magnetic powder, aluminum nickel cobalt magnetic powder, and titanium nickel iron magnetic powder, and the particle size is 0.02-0.04mm.
[0015] The method for preparing the composite phase change material comprises the following steps:
[0016] (1) slowly stirring and mixing N-pole magnetic powder and activated carbon powder for more than 60 minutes to obtain a mixture A; slowly stirring and mixing S-pole magnetic powder and expanded pearlite powder for more than 60 minutes to obtain a mixture B;
[0017] (2) heating the organic phase change material to above the phase change temperature, adding the mixture A and stirring and dispersing the mixture uniformly, cooling the mixture to below the phase change temperature and grinding the mixture C; the particle size of the mixture C is smaller than the pore size of the expanded pearlite powder;
[0018] (3) Mixture B and mixture C are slowly stirred and mixed for more than 60 minutes to obtain a composite phase change material.
[0019] According to the above scheme, the slow stirring rate is not higher than 100r / min.
[0020] Application of the above composite phase change material in gypsum-based self-leveling mortar or gypsum-based board.
[0021] According to the above scheme, the amount of the composite phase change material added to the gypsum-based self-leveling mortar or gypsum-based board is 3-5wt%.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] The present invention introduces N extremely strong magnetic powder into the activated carbon powder and adsorbs the organic phase change material, and then adsorbs it into the pores of the expanded perlite introduced with S extremely strong magnetic powder, thereby forming a double porous adsorption and strong magnetic attraction system, which has a high degree of integrity and excellent cyclic stability during the phase change process.
[0024] During the heat absorption and heat release process of the organic phase change material of the present invention, a large amount of fine magnetic powder adsorbed in the pores of activated carbon powder and expanded perlite can be used as a middle layer medium to achieve internal and external conduction, and the reasonable distribution of structural levels brings about a significant improvement in the efficiency of thermal energy storage and release.
[0025] The organic phase change material used in the present invention can be stably stored in perlite, and heat energy can be stored and released simultaneously with the use of perlite, which greatly simplifies the process flow and significantly reduces the energy waste caused by using gypsum materials for the "floor heating" covering layer. DETAILED DESCRIPTION
[0026] The following examples further illustrate the technical solution of the present invention, but are not intended to limit the scope of protection of the present invention.
[0027] A specific embodiment provides a method for preparing a composite phase change material, comprising the following steps:
[0028] (1) N-pole magnetic powder and activated carbon powder were stirred and mixed at 100 r / min for 60 min to obtain a mixture A; S-pole magnetic powder and expanded perlite powder were stirred and mixed at 100 r / min for 60 min to obtain a mixture B;
[0029] (2) heating the organic phase change material to above the phase change temperature, adding the mixture A and stirring and dispersing the mixture at 100 r / min, cooling the mixture to below the phase change temperature and grinding the mixture to obtain the mixture C; the particle size of the mixture C is smaller than the pore size of the expanded pearlite powder;
[0030] (3) Mixture B and mixture C were stirred and mixed at 100 r / min for 60 min to obtain a composite phase change material.
[0031] Specifically, the raw material composition is as follows in parts by weight: 52-62 parts of organic phase change material, 60-65 parts of activated carbon powder, 50-70 parts of expanded perlite powder, 17-28 parts of N-pole magnetic powder, and 17-28 parts of S-pole magnetic powder.
[0032] The specific implementation method also provides a gypsum-based self-leveling mortar, whose composition is calculated by mass as follows: 580-770 parts of gypsum powder, 10-15 parts of cement, 0.3-0.4 parts of stabilizer, 0.8-0.9 parts of retarder, 1-1.2 parts of water reducer, and 240-320 parts of water; the dosage of the composite phase change material is 3-5%; after being fully mixed, it is poured into a 300x300x30mm mold in which a temperature measuring probe is buried in advance to form; the curing conditions are a temperature of 20±2°C, a humidity of 70%-80%, and a curing time of 28d, and then the prepared gypsum sample is subjected to a continuous cycle temperature control test.
[0033] Specifically, the gypsum powder is mainly hemihydrate gypsum, specifically one or more industrial by-product gypsums such as phosphogypsum, desulfurized gypsum, fluorinated gypsum, and titanium gypsum. The cement is ordinary silicate cement with a strength grade of 42.5.
[0034] Specifically, the stabilizer is one of Starvis 3003F, EL0002, TAB-2, and T-386.
[0035] Specifically, the retarder is one of calcium dihydrogen phosphate, citric acid, tartaric acid, carboxymethyl cellulose and hydroxypropyl methyl cellulose.
[0036] Specifically, the water reducing agent is a polycarboxylic acid high-performance water reducing agent with a water reducing rate of 15-25%.
[0037] The dosage of each component in specific examples 1-5 is shown in Table 1.
[0038] Table 1
[0039] raw material Example 1 Example 2 Example 3 Example 4 Example 5 paraffin 3.65 servings 3.78 servings 3.99 copies 4.13 copies 4.34 servings Lauric acid 1.56 servings 1.62 servings 1.71 copies 1.77 servings 1.86 copies Activated carbon powder 6 servings 6.1 servings 6.3 servings 6.4 servings 6.5 servings N-pole magnetic powder 1.75 servings 2 servings 2.25 servings 2.5 servings 2.75 servings Expanded Perlite 5 servings 5.5 servings 6 servings 6.5 servings 7 servings S pole magnetic powder 1.75 servings 2 servings 2.25 servings 2.5 servings 2.75 servings Phosphogypsum powder 580 copies 620 copies 670 copies 720 copies 770 copies cement 10 servings 11 servings 12 servings 14 servings 15 servings Stabilizer 0.3 parts 0.33 copies 0.35 0.37 copies 0.4 parts Retarder 0.8 parts 0.83 copies 0.86 copies 0.88 0.9 parts Water reducing agent 1.2 servings 1.1 serving 1.1 serving 1.1 serving 1 serving water 240 copies 260 copies 280 copies 300 copies 320 copies
[0040] The cured gypsum sample prepared according to the above embodiment was subjected to a temperature control test, wherein the heating and cooling rates were controlled at 3°C / h. When the temperature was raised to 38°C, the temperature was kept constant for 6 hours. When the temperature was lowered to 20°C, the temperature was kept constant for 6 hours. The test results are shown in Table 2.
[0041] Table 2
[0042] Example 1 Example 2 Example 3 Example 4 Example 5 Initial temperature 20.0℃ 20.0℃ 20.0℃ 20.0℃ 20.0℃ Temperature after 3h 29.0℃ 29.0℃ 29.0℃ 29.0℃ 29.0℃ Temperature after 6 hours 35.3℃ 34.9℃ 32.1℃ 34.1℃ 33.8℃ Constant temperature for 6 hours 36.8℃ 36.0℃ 33.6℃ 35.7℃ 34.6℃ Temperature after 15h 28.2℃ 29.5℃ 31.4℃ 27.9℃ 30.2℃ Temperature after 18h 23.7℃ 26.3℃ 27.5℃ 24.0℃ 26.8℃ Constant temperature for 6 hours 20.5℃ 22.2℃ 25.6℃ 21.4℃ 24.5℃
[0043] As can be seen from Table 2, the temperature of Examples 1 and 2 after heating for 6 hours and then keeping the temperature constant for 6 hours is higher than that of Examples 3, 4 and 5, and the temperature after cooling for 6 hours and then keeping the temperature constant for 6 hours is much lower than that of Examples 3, 4 and 5, indicating that the heat absorption and heat release capacity of the structural system formed by the composite phase change material and the stabilization and synergistic material at low dosage is limited. In addition, although the dosage of the composite phase change material and the stabilization and synergistic material is increased in Example 4, as the proportion of mortar increases, the effect shown is only slightly better than that of Example 1, indicating that the high efficiency and high stability characteristics of the phase change material are also closely related to the proportion of the reference material. The comprehensive performance of Example 3 is the best. After heating for 6 hours and keeping the temperature constant for 6 hours, the internal temperature of the mortar is significantly reduced, and after cooling for 6 hours and keeping the temperature constant for 6 hours, the internal temperature of the mortar is significantly increased. At this time, the dosage of the composite phase change material, the stabilization and synergistic material and the coating material is most appropriate. The appropriate dosage brings extremely high stability to the inner and outer layer structures, and the composite phase change material can also play the corresponding role and effect to the greatest extent.
[0044] Comparative Example 1 uses a composite phase change material without adding magnetic powder:
[0045] (1) heating the organic phase change material to a temperature above the phase change temperature, adding activated carbon powder and stirring and dispersing the mixture at 100 r / min, cooling the mixture to a temperature below the phase change temperature and grinding the mixture to obtain a mixture; the particle size of the mixture is smaller than the pore size of the expanded pearlite powder;
[0046] (2) The mixture and expanded perlite powder were stirred at 100 r / min for 60 min to obtain a composite phase change material 1.
[0047] Comparative Example 2 uses a composite phase change material without adding expanded perlite:
[0048] (1) N-pole magnetic powder and activated carbon powder were stirred and mixed at 100 r / min for 60 min to obtain a mixture A;
[0049] (2) heating the organic phase change material to above the phase change temperature, adding the mixture A and stirring at 100 r / min to disperse the mixture uniformly, cooling the mixture to below the phase change temperature and grinding the mixture to obtain the mixture C;
[0050] (3) The S-pole magnetic powder and the mixture C were stirred and mixed at 100 r / min for 60 min to obtain a composite phase change material 2.
[0051] Comparative Example 3: Neither magnetic powder nor expanded perlite is added:
[0052] The organic phase change material is heated to above the phase change temperature, activated carbon powder is added and stirred at 100 r / min to be evenly dispersed, and then ground after cooling to below the phase change temperature to obtain a composite phase change material 3.
[0053] The best performing embodiment 3 among embodiments 1-5 is taken as the benchmark group, and comparative examples 1-3 are set. The initial temperature of the four groups is 20.0°C, and then they are placed in an automatic temperature control device and heated at 3°C / h at the same time. When the device is heated to 38°C, the temperature is kept constant for 6h, and then cooled at 3°C / h at the same time. When the device is cooled to 20°C, the temperature is kept constant for 6h. This process is repeated continuously, and the number of cycles and the temperature per hour are collected from the automatic temperature control device system. Comparison of the number of failure cycles and the changes in temperature rise and fall between embodiment 3 and comparative examples 1-3 can be used as evaluation indicators of phase change stability and thermal energy storage and release efficiency. Since there is almost no significant difference in the temperature of the four groups in the first 17 cycles, but there is a significant difference in the 18th cycle, Table 3 shows the data recorded in the 18th cycle.
[0054] Table 3
[0055]
[0056]
[0057] As can be seen from Table 3, Example 3 has not failed after 291 cycles (it can be considered to have failed when the temperature of the temperature control device is almost consistent every hour), and the number of cycle failures of Comparative Examples 1-3 is 22 times, 58 times, and 73 times, respectively, indicating that the phase change material prepared by the present invention has strong stability during the solid-liquid conversion cycle, and the problem of easy leakage of organic phase change materials is greatly improved. In addition, compared with Comparative Examples 1-3, Example 3 stores a large amount of heat energy in the process of continuing to heat up after reaching the phase change point temperature, and quickly releases the stored large amount of heat energy in the process of cooling, and the efficiency of heat storage and release is significantly improved.
[0058] The above embodiments are merely examples for clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above descriptions. It is not necessary and impossible to list all the implementation methods here, and the obvious changes or modifications derived therefrom are still within the protection scope of the invention.
Claims
1. A composite phase change material, characterized in that The composition is calculated by weight as follows: 52-62 parts of organic phase change material, 60-65 parts of activated carbon powder, 50-70 parts of expanded perlite powder, 17-28 parts of N-pole magnetic powder, and 17-28 parts of S-pole magnetic powder.
2. The composite phase change material according to claim 1, characterized in that The organic phase change material is a compound of paraffin and fatty acid organic phase change material, with a phase change temperature of 29°C, a phase change latent heat of 220J / g, and a thermal conductivity of 0.2W / (m·K); wherein the fatty acid phase change material is one of lauric acid, capric acid, stearic acid, myristic acid, palmitic acid, and acetic acid.
3. The composite phase change material according to claim 1, characterized in that The activated carbon powder has a particle size of 0.7-0.8 mm, a pH value of 3-7, and a pore size of 0.1-0.11 mm.
4. The composite phase change material according to claim 1, characterized in that The expanded perlite has a particle size of 3-5 mm and a density of 0.8 g / cm 3 , the pore size is 1-1.5mm.
5. The composite phase change material according to claim 1, characterized in that The N-pole magnetic powder is one of samarium cobalt magnetic powder, ferrite magnetic powder, neodymium iron boron magnetic powder, aluminum nickel cobalt magnetic powder, and titanium nickel iron magnetic powder, and has a particle size of 0.02-0.04 mm.
6. The composite phase change material according to claim 1, characterized in that The S-pole magnetic powder is one of samarium cobalt magnetic powder, ferrite magnetic powder, neodymium iron boron magnetic powder, aluminum nickel cobalt magnetic powder, and titanium nickel iron magnetic powder, and has a particle size of 0.02-0.04 mm.
7. The method for preparing the composite phase change material according to any one of claims 1 to 6, characterized in that The following steps are involved: (1) slowly stirring and mixing N-pole magnetic powder and activated carbon powder for more than 60 minutes to obtain a mixture A; slowly stirring and mixing S-pole magnetic powder and expanded pearlite powder for more than 60 minutes to obtain a mixture B; (2) heating the organic phase change material to above the phase change temperature, adding the mixture A and stirring and dispersing the mixture uniformly, cooling the mixture to below the phase change temperature and grinding the mixture C; the particle size of the mixture C is smaller than the pore size of the expanded pearlite powder; (3) Mixture B and mixture C are slowly stirred and mixed for more than 60 minutes to obtain a composite phase change material.
8. The method for preparing the composite phase change material according to claim 7, characterized in that The slow stirring rate is not higher than 100r / min.
9. Use of the composite phase change material according to any one of claims 1 to 6 in gypsum-based self-leveling mortar or gypsum-based board material.
10. Use of the composite phase change material according to claim 9 in gypsum-based self-leveling mortar or gypsum-based board material, wherein the amount of the composite phase change material in the gypsum-based self-leveling mortar or gypsum-based board material is 3-5wt%.
Citation Information
Patent Citations
Preparation method of gypsum clay composite phase change energy storage material
CN104152114B
Shaping phase change material for building and application thereof
CN113788648A